New pozzanic industrial wastes for eco-efficient concrete - Shasavandi, Arman (2012)
Concrete is one of the most widely used construction materials in the world. However, the production of Portland cement as the essential constituent of concrete requires a considerable energy level and also releases a significant amount of chemical carbon dioxide emissions and other greenhouse gases (GHGs) into the atmosphere. Thus, seeking an eco-efficient and sustainable concrete may be one of the main roles that construction industry should play in sustainable construction. To make the concrete more eco-efficient, different life cycle phases of concrete products should be considered, such as extraction of raw material, production of constituents, production of concrete, transportation, erection, maintenance, deconstruction or demolition and recycling. Since binder production represents the major part of the environmental impacts , investigations on partial binder replacement by pozzolanic additions or use of environmental friendly binders lead to an eco-efficient concrete. The present study, as the preliminary results of a PhD research project, is an attempt to evaluate the pozzolanic reactivity of some industrial wastes, namely ceramic waste and slate powder, as well as the possibility of using such materials as partial replacement for Portland Cement. Results indicate that a high-strength eco-efficient concrete can be produced using slate powder or ceramic waste with metakaolin as Portland Cement replacement.